Corporate Voluntary Disclosure and Separation of Cash Flow Rights From Control Rights - MohamadAli Aghaei (Shahid Bahonar University of Kerman, 2016)
This study examines special aspect of interest conflict in the relationship between shareholders and voluntary disclosure in financial reporting. After theoretical review, testing three hypotheses designed in terms of the relationship concerning separation of cash flow rights from control rights in corporate voluntary disclosure, and the impact of external financing needs and large non-management shareholder (as control mechanism) on the relationship. Study sample was taken from companies listed in the Tehran Stock Exchange, and the financial statements and reports of boards of directors of the companies in the period 2008-2012. The results of hypotheses testing, using multiple regression model, suggested that corporate voluntary disclosure is negatively correlated with the separation of cash flow rights from control rights, and that this relationship, after presence of big external shareholders, tends to shrink. Also, it was found that there is no impact from needs to external financing on the relationship between voluntary disclosure and separation of cash flow rights from control rights.